Case Studies in Systems Chemistry - Fleck, George (Open textbook library., 1973)
This publication was produced as a teaching tool for college chemistry.The book is a text for a computer-based unit on the chemistry of acid-base titrations, and is designed for use with FORTRAN or BASIC.computer systems, and with a programmable electronic calculator, in a variety of educational settings. The text attempts to present computer programs that are relatively free of reliance on specialized large computer systems programs. The case-study approach presented is highly research and laboratory oriented. Similar subject matter is conventionally taught in most introductory college chemistry courses, but this text material attempts greater depth of instruction through utilization of the computational resources of a computer.